ANALISIS UJI BEDA PELATIHAN, PENGALAMAN KERJA DAN TINGKAT PENDIDIKAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT.POS INDONESIA CABANG KOTA DUMAI - Zulaika Siti; ningsih Suryati Dewita; Marhadi Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
PT. Pos Indonesia Dumai City Branch provides mail and package deliveryservices as well as financial services such as electricity payments, tax payments,motor vehicle loan installment payments, sending and receiving money fromwithin and outside the country, payment of passport manufacturing fees andpurchase of stamps and stamps. The increasing competition of companies in thesame field in Dumai City such as JNE, J&T, TIKI delivery services and financialservices such as financial transaction agents from banks has a big impact on PT.Pos Indonesia Dumai City Branch. This study aims to determine the differences intraining, differences in work experience and differences in education levels to thework productivity of employees at PT. Pos Indonesia Dumai City Branch. Thepopulation of this study was employees of PT. Pos Indonesia Dumai City Branchwith a total of 68 respondents. The data analysis technique used is descriptiveanalysis. Data collection techniques use primary data and secondary data. Thedata analysis used is a validity test, reliability test, normality test and T test(Paired Sample t-Test). The results showed that there were differences in training,differences in work experience and differences in the level of education to thework productivity of employees at PT. Pos Indonesia Dumai City Branch. Keywords : Training, Work Experience, Education Level and Work Productivity